Thematic evaluation of aquaculture - UNDP (FAO RomeIT, 1987)
Seeks to identify recurring issues which can be assessed and resolved to strenghten and accelerate the development of aquaculture and also to improve the selection, formulation, execution and effectiveness of national projects and regional aquaculture programmes. Identifies the strong and weak features of UNDP and FAO-assisted projects.